DESKRIPSI KUALITAS DAN KUANTITAS LIMBAH CAIR USAHA LAUNDRY DI KELURAHAN SUMAMPIR KECAMATAN PURWOKERTO UTARA KABUPATEN BANYUMAS TAHUN 2018 - Adninda Huda Nisa; Mela Firdaust; Bayu Chondro Purnomo (Buletin Keslingmas, 2019)
Background The development of laundry business in the increasingly rapid in Sumampir village make the aquatic environment in the region to be foamy and overgrown with microalgae. Research purposes to describe and to know the quality and quantity of waste water of  laundry in Sumampir Village. Type of research, descriptive research. The subjects  9 laundry business, parameters measured are phosphate content of waste water, detergent type, detergent composition, detergent dosage, volume of waste water, frequency of waste water disposal and waste water management from laundry business.The results 89% of laundry business with average phospate 0,76 mg/L (content appropriate) and 11% laundry business with phosphate level of 5.84 mg/L (did not appropriate), 67% of the laundry business used liquid detergent, soft and matic top load type and 33% of respondents used powder detergent, hard and matic front load, 44% of respondents did not use detergents according to the type of washing machine. Detergent composition used by laundry business that is 25% Total Surfactant, Antibacterial Agent, Sodium Alkyl Benzene Sulfonate and Natrium Carbonate 20%. The majority of the detergent dosage used by the laundry business is 23 ml. The average volume of waste water produced from 9 laundry business 1038.57 liters/day. Average frequency of waste water disposal from 9 laundry business 13 times/day and 100% laundry business does not manage the waste water and does not have a  waste water treatment facilities. Conclusion, the quality and quantity of  wastewater at laundry business in Sumampir Village is at risk of environmental pollution